Acrylic composition and molded article
The acrylic resin composition addresses the issues of heat resistance, surface hardness, and dimensional stability by incorporating a balanced blend of acrylic copolymer and elastomer, resulting in improved mechanical properties and reduced water absorption.
Patent Information
- Application Number
- JP2022510740
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-26
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2041-03-26
AI Technical Summary
Existing acrylic resin compositions with improved heat resistance suffer from reduced surface hardness, mechanical toughness, and increased water absorption, leading to diminished dimensional stability.
A specific acrylic resin composition comprising 51 to 99% by mass of an acrylic copolymer and 1 to 49% by mass of an elastomer, with a balanced mixture of methacrylate units, α-methylstyrene units, and structural units with ring structures, along with other vinyl monomers, to enhance heat resistance, surface hardness, and reduce water absorption.
The composition achieves high heat resistance, low water absorption, and excellent dimensional stability while maintaining surface hardness and mechanical toughness.
Smart Images

Figure 0007627263000001 
Figure 0007627263000002 
Figure 0007627263000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic resin composition and a molded article. [Background technology]
[0002] Methacrylic resins are excellent in transparency, weather resistance, surface hardness, etc. By molding an acrylic resin composition containing the methacrylic resin, various components used for display components, electronic and electrical components, transportation components, etc. In recent years, there has been a demand for improved performance of various components, and in particular, there has been a strong demand for improved heat resistance.
[0003] For the purpose of improving heat resistance, an acrylic resin composition having a ring structure in the main chain skeleton has been proposed. For example, Patent Document 1 discloses a modified methacrylic resin containing a structural unit derived from methyl methacrylate or the like and a structural unit having at least one ring structure selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, and an N-substituted or unsubstituted glutarimide unit in the main chain. In addition, Patent Document 2 discloses a copolymer consisting of a (meth)acrylic acid ester monomer unit, an unsaturated dicarboxylic anhydride monomer unit, and an unsaturated aromatic vinyl monomer unit.
[0004] Furthermore, since the acrylic resin with high heat resistance has a relatively low strength and low toughness, there is concern that the impact resistance of the molded product is insufficient, and productivity is deteriorated in terms of the moldability and handling of the film. A technique of incorporating an elastomer has been disclosed as a technique for improving the strength of a heat-resistant acrylic resin. Patent Document 3 discloses a technique of incorporating a crosslinked elastic body having a multilayer structure as an elastomer into an acrylic resin containing a glutaric anhydride unit. Patent Document 4 discloses a technique of adding an acrylic rubber as an elastomer to an acrylic resin containing a maleic anhydride unit. Furthermore, Patent Document 5 discloses a technique of adding a block copolymer containing a methacrylic acid ester polymer block and an acrylic acid ester polymer block as an elastomer to an acrylic resin containing a structural unit having at least one ring structure selected from the group consisting of a lactone ring unit, a maleic anhydride unit, a glutaric anhydride unit, a glutarimide unit, an N-substituted maleimide unit, and a tetrahydropyran ring structural unit in the main chain. Patent Document 6 discloses a technique of adding a graft copolymer as an elastomer to an acrylic resin having a glass transition temperature of 120° C. or higher and a refractive index of 1.50 or higher, and describes an imidized resin of a methyl methacrylate-styrene copolymer as the acrylic resin in the examples. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-179103 A [Patent Document 2] WO2014 / 021264 A1 [Patent Document 3] JP 2000-178399 A [Patent Document 4] Japanese Patent Application Publication No. 05-119217 [Patent Document 5] JP 2016-8225 A [Patent Document 6] JP 2009-203348 A Summary of the Invention [Problem to be solved by the invention]
[0006] Although the strength of the heat-resistant acrylic resin is improved in any of the techniques disclosed in the prior art, there are problems such as a decrease in surface hardness and a decrease in dimensional stability due to an increase in water absorption, and the inherent excellent properties of the acrylic resin cannot be fully exhibited. In view of the above circumstances, an object of the present invention is to provide an acrylic resin composition and a molded article thereof which maintain heat resistance and mechanical strength (toughness) and have excellent surface hardness and dimensional stability. [Means for solving the problem]
[0007] As a result of investigations conducted in order to achieve the above object, the present invention has been completed, which includes the following aspects. [1] An acrylic resin composition comprising 51 to 99 mass% of an acrylic copolymer (A) comprising 30 to 87 mass% of methyl methacrylate units, 6 to 40 mass% of structural units (R) having at least one ring structure in the main chain selected from the group consisting of glutaric anhydride units and N-substituted or unsubstituted glutarimide units, 7 to 30 mass% of α-methylstyrene units, and 0 to 20 mass% of other vinyl monomer units (C) copolymerizable with methyl methacrylate, and 1 to 49 mass% of an elastomer (B). [2] The acrylic resin composition according to [1], wherein the structural unit (R) is an N-substituted glutarimide unit represented by formula (I). [ka] (In formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 is an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring. [3] The acrylic resin composition according to [1] or [2], wherein the other vinyl monomer unit (C) copolymerizable with the methyl methacrylate unit is formed of at least one monomer selected from the group consisting of an acrylic acid ester monomer, an aromatic vinyl monomer, and a vinyl cyanide monomer. [4] The acrylic resin composition according to any one of [1] to [3], wherein the other vinyl monomer unit (C) copolymerizable with the methyl methacrylate unit is formed of at least one selected from the group consisting of methyl acrylate, ethyl acrylate, styrene, and acrylonitrile. [5] The acrylic resin composition according to any one of [1] to [3], wherein the other vinyl monomer unit (C) copolymerizable with the methyl methacrylate unit is formed from styrene. [6] The acrylic resin composition according to any one of [1] to [5], wherein the elastomer (B) contains a multilayer copolymer elastomer having a methacrylic acid ester unit and an acrylic acid ester unit. [7] The acrylic resin composition according to any one of [1] to [6], wherein the elastomer (B) contains a block copolymer elastomer composed of a polymer block (b1) having a methacrylic acid ester unit and a polymer block (b2) having an acrylic acid ester unit. [8] The acrylic resin composition according to any one of [1] to [7], wherein a molded product has a softening temperature of 110° C. or higher, as measured by the method specified in JIS K7206 B50 method. [9] The acrylic resin composition according to any one of [1] to [8], which has a saturated water absorption rate of 2.5% or less.
[10] A molded article comprising the acrylic resin composition according to any one of [1] to [9].
[11] A film comprising the acrylic resin composition according to any one of [1] to [9]. Effect of the Invention
[0008] According to the present invention, it is possible to obtain a molded product having high heat resistance and low water absorption, and a film having excellent dimensional stability and high surface hardness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The acrylic resin composition of the present invention contains an acrylic copolymer (A) and an elastomer (B). The content of the acrylic copolymer (A) in the acrylic resin composition is 51 to 99% by mass, preferably 55 to 95% by mass, and more preferably in the range of 60 to 90% by mass. When the content of the acrylic copolymer (A) in the acrylic resin composition of the present invention is 51% by mass or more, the composition has excellent heat resistance and surface hardness, and when the content is 99% by mass or less, the composition has improved brittleness.
[0010] (Acrylic copolymer (A)) The acrylic copolymer (A) according to the present invention contains methyl methacrylate units, α-methylstyrene units, and structural units (R). The acrylic copolymer according to the present invention may further contain other vinyl monomer units (C) copolymerizable with methyl methacrylate. The other vinyl monomer units (C) copolymerizable with methyl methacrylate may be methacrylamide units represented by the following formula (A) or 2-(hydroxyalkyl)methyl acrylate units represented by the following formula (B).
[0011] [ka] (In the formula, R 3 R is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring, preferably a hydrogen atom, a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, and more preferably a methyl group, an n-butyl group, or a cyclohexyl group. 4 and R 5are each independently a hydrogen atom or an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom or an organic group having 1 to 10 carbon atoms, more preferably a hydrogen atom or an organic group having 1 to 5 carbon atoms. Here, the organic group is not particularly limited as long as it has 1 to 20 carbon atoms, and examples thereof include a linear or branched alkyl group, a linear or branched aryl group, a -OCOCH3 group, and a -CN group. The organic group may contain a heteroatom such as an oxygen atom. R 4 is preferably a methyl group, R 5 is preferably a hydrogen atom.
[0012] The acrylic copolymer (A) according to the present invention has a ratio of methyl methacrylate units of 30 to 87% by mass, preferably 40 to 85% by mass, and more preferably 55 to 80% by mass, based on the total structural units. If the ratio of methyl methacrylate units is less than this range, the total light transmittance of the resulting acrylic copolymer is deteriorated, whereas if the ratio of methyl methacrylate units is more than this range, the heat resistance of the resulting acrylic copolymer is reduced.
[0013] The acrylic copolymer (A) according to the present invention has an α-methylstyrene unit content of 7-30% by mass, preferably 8-27% by mass, more preferably 11-25% by mass, based on the total structural units. If the content of α-methylstyrene units is less than this range, the saturated water absorption of the resulting acrylic copolymer will be high. In addition, an acrylic copolymer having an α-methylstyrene unit content of more than 30% by mass will have low polymerizability and low productivity.
[0014] The structural unit (R) is a structural unit having at least one ring structure selected from the group consisting of glutaric anhydride units and N-substituted or unsubstituted glutarimide units in the main chain. The acrylic copolymer according to the present invention may contain methacrylamide units represented by the above formula (A) and / or 2-(hydroxyalkyl)acrylic ester units represented by the above formula (B) in the main chain.
[0015] The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure. An example of the unit having a 2,6-dioxodihydropyrandiyl structure is a structural unit represented by the formula (II).
[0016] [ka] In formula (II), R 6 are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and two R 6 and R 2 are preferably both methyl groups.
[0017] The unit having a 2,6-dioxodihydropyrandiyl structure can be incorporated into the acrylic copolymer by the method described in JP 2007-197703 A, JP 2010-96919 A, etc., for example, intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid, intramolecular cyclization of a structural unit derived from (meth)acrylic acid and a structural unit derived from methyl (meth)acrylate, etc. JP 2007-197703 A and JP 2010-96919 A are incorporated herein by reference in their entirety.
[0018] The N-substituted or unsubstituted glutarimide unit is a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure. An example of a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure is a structural unit represented by formula (I).
[0019] [ka]
[0020] In formula (I), R 1 are each independently a hydrogen atom or a methyl group, and two R 1 Preferably, both R are methyl groups. 2is a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring, and is preferably a methyl group, an n-butyl group, a cyclohexyl group, or a benzyl group, more preferably a methyl group, an n-butyl group, or a cyclohexyl group, and most preferably a methyl group, since it is possible to reduce the water absorption rate. The structural unit represented by formula (I) can be prepared by, for example, reacting the corresponding acid anhydride (IIa) with R 2 It may be produced by the reaction of an imidizing agent represented by NH2, or by the intramolecular cyclization reaction of a copolymer having a partial structure of formula (III). It is preferable to heat the copolymer to convert the structural unit represented by formula (III) to the structural unit represented by formula (I) by the intramolecular cyclization reaction. Scheme (i)
[0021] [ka] (In the formula, R 1 , R 2 is as defined above.)
[0022] The N-substituted or unsubstituted glutarimide unit can be obtained by the method described in WO2005 / 10838A1, JP2010-254742A, JP2008-273140A, JP2008-274187A, etc., specifically, by reacting a structural unit derived from two adjacent methyl methacrylates or a glutaric anhydride unit with an imidizing agent such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., an aromatic hydrocarbon group-containing amine such as aniline, toluidine, trichloroaniline, etc., an alicyclic hydrocarbon group-containing amine such as cyclohexylamine, etc., urea, 1,3-dimethylurea, 1,3-diethylurea, 1,3-dipropylurea, etc. Among these, methylamine is preferred. WO2005 / 10838A1, JP2010-254742A, JP2008-273140A, and JP2008-274187A are incorporated herein by reference in their entirety. During this imidization reaction, some of the methyl methacrylate units may be hydrolyzed to form carboxyl groups, and it is preferable to return these carboxyl groups to the original methyl methacrylate units by an esterification reaction in which the carboxyl groups are treated with an esterifying agent. The esterifying agent is not particularly limited as long as it can exert the effects of the present application, but dimethyl carbonate and trimethyl acetate can be preferably used. In addition to the esterifying agent, a tertiary amine such as trimethylamine, triethylamine, or tributylamine can also be used as a catalyst.
[0023] The acrylic copolymer (A) according to the present invention has a ratio of the structural unit (R) of 6 to 40% by mass, preferably 7.5 to 35% by mass, more preferably 8 to 30% by mass, based on the total structural units. The orientation birefringence of the acrylic copolymer can be changed by changing the ratio of the structural unit (R) to methyl methacrylate. In addition, the higher the content of the structural unit (R), the more the heat resistance of the acrylic copolymer improves, but the more the flexibility decreases, and the compatibility with other copolymers and the moldability tend to decrease.
[0024] Examples of other vinyl monomer units (C) copolymerizable with methyl methacrylate units (hereinafter, sometimes referred to as (C) monomer units) include acrylic ester monomer units (C-1), aromatic vinyl monomer units (C-2), vinyl cyanide monomer units (C-3), and other monomer units (C-4). The other vinyl monomer units (C) copolymerizable with methyl methacrylate units may be used alone or in combination of two or more.
[0025] The monomer unit (C) can be appropriately selected from a material depending on the properties required for the acrylic copolymer of the present invention. When properties such as thermal stability, flowability, chemical resistance, optical properties, and compatibility with other resins are particularly required, at least one selected from the group consisting of an acrylic acid ester monomer unit, an aromatic vinyl monomer unit, and a vinyl cyanide monomer unit is suitable.
[0026] The acrylic acid ester monomer unit (C-1) constituting the acrylic copolymer according to the present invention is not particularly limited, but from the viewpoints of heat resistance, fluidity, heat resistance stability, productivity, etc., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, cyclohexyl acrylate, phenyl acrylate, etc. are preferred, more preferably methyl acrylate, ethyl acrylate, and n-butyl acrylate, and from the viewpoint of productivity, even more preferably methyl acrylate and ethyl acrylate. The acrylic acid ester monomer unit (C-1) may be used alone or in combination of two or more kinds.
[0027] When the acrylic acid ester monomer unit (C-1) is used, its content is preferably 20% by mass or less, and more preferably 10% by mass or less, based on all structural units, from the viewpoints of heat resistance and thermal stability.
[0028] The aromatic vinyl monomer unit (C-2) constituting the acrylic copolymer according to the present invention is not particularly limited, but from the viewpoint of heat resistance, fluidity, heat stability, productivity, etc., styrene (St), o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylbenzylbenzene, isopropenylhexylbenzene, isopropenyloctylbenzene, etc. are preferred, and styrene is more preferred from the viewpoint of copolymerization reactivity with α-methylstyrene during the production of a precursor polymer described below. The aromatic vinyl monomer unit (C-2) may be used alone or in combination of two or more kinds.
[0029] When the aromatic vinyl monomer unit (C-2) is used, its content is preferably from 3 mass% to 20 mass% and more preferably from 4 mass% to 15 mass% based on all structural units, from the viewpoints of heat resistance and thermal stability.
[0030] The vinyl cyanide monomer unit (C-3) constituting the acrylic copolymer according to the present invention is not particularly limited, but from the viewpoints of heat resistance, flowability, heat stability, chemical resistance, productivity, etc., acrylonitrile (AN), methacrylonitrile, vinylidene cyanide, etc. are preferred, and among them, acrylonitrile is preferred from the viewpoints of availability and chemical resistance. The vinyl cyanide monomer unit (C-3) may be used alone or in combination of two or more kinds.
[0031] When the vinyl cyanide monomer unit (C-3) is used, its content is preferably 20% by mass or less, and more preferably 10% by mass or less, based on all structural units, from the viewpoints of heat resistance and thermal stability.
[0032] The monomer constituting the monomer unit (C-4) other than (C-1) to (C-3) constituting the acrylic copolymer according to the present invention is not particularly limited, and may be a monomer corresponding to the methacrylamide unit represented by formula (A) or a monomer corresponding to the 2-(hydroxyalkyl)acrylic acid ester unit represented by formula (B), and examples thereof include amides such as acrylamide and methacrylamide; ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, or other ethylene glycols or oligomers thereof, both terminal hydroxyl groups of which are esterified with acrylic acid or methacrylic acid; neopentyl glycol di(meth)acrylate. To et al. esters of the hydroxyl groups of the above two alcohols with acrylic acid or methacrylic acid; and esters of polyhydric alcohol derivatives such as trimethylolpropane and pentaerythritol with acrylic acid or methacrylic acid.
[0033] Among the monomers constituting the above-mentioned (C) monomer unit, at least one selected from the group consisting of methyl acrylate (MA), ethyl acrylate, styrene, and acrylonitrile is preferred from the viewpoint of availability, and styrene is more preferred from the viewpoint of moisture resistance.
[0034] In the acrylic copolymer according to the present invention, the proportion of other vinyl monomer units (C) copolymerizable with methyl methacrylate units is preferably 0-20% by mass, more preferably 0-15% by mass, and even more preferably 0-10% by mass, based on the total structural units. When the proportion of other vinyl monomer units (C) copolymerizable with methyl methacrylate units exceeds 20% by mass, the heat resistance and rigidity of the acrylic copolymer decrease. The proportions of the methyl methacrylate units, α-methylstyrene units, structural units (R), and monomer units (C) are as follows: 1 H-NMR, 13 It can be measured by C-NMR, etc.
[0035] The acrylic copolymer (A) according to the present invention has a weight average molecular weight (Mw) of preferably 40,000 to 200,000, more preferably 50,000 to 180,000, and further preferably 55,000 to 160,000. When Mw is 40,000 or more, the strength, toughness, etc. of the molded article of the present invention are improved. When Mw is 200,000 or less, the fluidity of the acrylic copolymer is improved, and molding processability is improved.
[0036] The weight average molecular weight (Mw) is a value calculated by converting a chromatogram measured by gel permeation chromatography into the molecular weight of standard polystyrene.
[0037] The acrylic copolymer (A) according to the present invention has an acid value of preferably 0.01 to 0.30 mmol / g, more preferably 0.05 to 0.28 mmol / g. The acid value is a value proportional to the content of carboxylic acid units and carboxylic anhydride units in the acrylic copolymer. The acid value can be calculated, for example, by the method described in JP-A-2005-23272. When the acid value is within the above range, the balance of heat resistance, mechanical properties, and moldability is excellent.
[0038] The acrylic copolymer (A) according to the present invention has a glass transition temperature of preferably 130°C as a lower limit, more preferably 131°C, and even more preferably 132°C as an upper limit, and is not particularly limited, but is preferably 160°C. In this specification, the "glass transition temperature (Tg)" is measured in accordance with JIS K7121. Specifically, the temperature is raised once to 230°C, then cooled to room temperature, and then the DSC curve is measured under conditions of raising the temperature from room temperature to 230°C at a rate of 10°C / min. The midpoint determined from the DSC curve measured during the second heating is determined as the "glass transition temperature (Tg)".
[0039] The saturated water absorption of the acrylic copolymer (A) according to the present invention is measured under the following conditions. The acrylic copolymer is press-molded into a sheet having a thickness of 1.0 mm. A test piece of 50 mm x 50 mm is cut out from the center of the obtained press-molded sheet and dried in a dryer at 80 ° C for 16 hours or more. The dried test piece is cooled to room temperature in a desiccator, and then its weight is measured to the nearest 0.1 mg, and this weight is defined as the initial weight Wo. The test piece is immersed in distilled water at 23 ° C., and after immersion for 24 hours, the test piece is removed from the water and all surface moisture is wiped off with a clean, dry cloth or filter paper. Within 1 minute of removing from the water, the test piece is weighed again to the nearest 0.1 mg. The test piece is immersed again, and the weight is measured again in the same manner as above after 24 hours. The weight when the weight change rate of the test piece becomes within 0.02% of Wo is defined as the saturated weight Ws. The saturated water absorption is calculated from formula (2).
[0040]
number
[0041] The acrylic copolymer (A) according to the present invention preferably has a 1% thermal weight loss temperature in a nitrogen atmosphere of 265° C. or higher, more preferably 270° C. or higher.
[0042] The acrylic copolymer (A) according to the present invention can be obtained by a method including subjecting a copolymer (hereinafter sometimes referred to as a precursor polymer) of methyl methacrylate, α-methylstyrene, and, if necessary, other vinyl monomer units (C) copolymerizable with methyl methacrylate to a ring structure-forming reaction. That is, the production method includes the steps of continuously supplying a reaction raw material containing a monomer mixture containing 60 to 93 mass % of methyl methacrylate, 30 to 7 mass % of α-methylstyrene, and 0 to 20 mass % of a copolymerizable monomer (C), a radical polymerization initiator, and optionally a chain transfer agent, to a tank-type reactor; A step of bulk polymerizing the monomer mixture in a tank reactor to a polymerization conversion rate of 30 to 60 mass % to obtain a reaction product; and removing the monomer mixture in the reaction product to obtain a precursor polymer; A step of subjecting the obtained precursor polymer to a ring structure forming reaction. Each step can be carried out by a known technique.
[0043] The precursor polymer is produced by polymerization of reaction raw materials including a monomer mixture, a radical polymerization initiator, and optionally a chain transfer agent, and the monomer mixture contains 51 to 90 mass%, preferably 65 to 85 mass%, of methyl methacrylate in the monomer mixture. The monomer mixture also contains 49 to 10 mass%, preferably 35 to 15 mass%, of α-methylstyrene. Furthermore, the monomer mixture also contains 0 to 20 mass%, preferably 0 to 15 mass%, of a copolymerizable monomer (C).
[0044] The monomer mixture preferably has b* of -1 to 2, more preferably -0.5 to 1.5. When b* is in this range, it is advantageous for obtaining molded products with little coloring at high production efficiency when the resulting acrylic copolymer composition is molded. Note that b* is a value measured in accordance with the International Commission on Illumination (CIE) standard (1976) or JIS Z8722.
[0045] The polymerization initiator used is not particularly limited as long as it generates reactive radicals. Examples of the polymerization initiator include peroxide initiators such as diisopropylbenzene hydroperoxide and t-butyl hydroperoxide, and azo initiators such as 2,2'-azobis(2-methylpropionitrile).
[0046] The polymerization initiator used is a polymerization initiator having an average uncleaved initiator concentration of 5.1 × 10 at the polymerization temperature in a tank reactor described below. -5 ~2.4×10 -4 The amount of the polymerization initiator used is adjusted to the polymerization temperature and added to the monomer mixture so as to achieve the above initiator concentration.
[0047] The chain transfer agent used is preferably a monofunctional alkyl mercaptan such as n-octyl mercaptan or n-dodecyl mercaptan. These chain transfer agents can be used alone or in combination of two or more. The amount of the chain transfer agent used is preferably 0 to 1 part by mass, more preferably 0.01 to 0.8 parts by mass, and even more preferably 0.02 to 0.6 parts by mass, based on 100 parts by mass of the monomer mixture.
[0048] The temperature inside the tank reactor, i.e., the temperature of the liquid inside the reaction tank, is preferably 110 to 140° C., more preferably 114 to 135° C. If the temperature is higher than this range, it becomes difficult to produce high molecular weight compounds containing α-methylstyrene, which causes a decrease in heat resistance.
[0049] In a tank reactor, bulk polymerization is preferably carried out until the polymerization conversion rate reaches 30 to 65% by mass, and more preferably 35 to 60% by mass.
[0050] The average residence time (θ) of the reaction raw materials in the tank reactor is preferably 1.5 to 5 hours, more preferably 2 to 4.5 hours, and even more preferably 2.5 to 4 hours. If the average residence time is too short, the amount of polymerization initiator required increases. Furthermore, an increase in the amount of polymerization initiator makes it difficult to control the polymerization reaction and tends to make it difficult to control the molecular weight. On the other hand, if the average residence time is too long, it takes time for the reaction to reach a steady state, and productivity tends to decrease. The average residence time can be adjusted by the capacity of the tank reactor and the amount of reaction raw materials supplied.
[0051] The bulk polymerization is preferably carried out in an atmosphere of an inert gas such as nitrogen gas.
[0052] The production method according to the present invention includes a step of removing the monomer mixture from the reaction product. The removal method is not particularly limited, but a heat devolatilization method is preferred. After removing the monomer mixture, the acrylic resin composition can be made into pellets or powder according to a known method to facilitate handling as a molding material. The content of the monomer mixture in the obtained acrylic resin composition is preferably 1% by mass or less, more preferably 0.5% by mass or less.
[0053] The precursor polymer has a glass transition temperature of preferably 115°C as a lower limit, more preferably 120°C, and even more preferably 125°C as an upper limit, and preferably 150°C. The glass transition temperature can be changed by adjusting the molecular weight, the amount of α-methylstyrene copolymerized, etc. The higher the glass transition temperature of the precursor polymer, the more improved the heat resistance. An acrylic copolymer obtained by using a precursor polymer having a high glass transition temperature has high heat resistance even if the amount of structural unit (R) is small, and is therefore unlikely to cause deterioration of saturated water absorption, etc.
[0054] The precursor polymer is not particularly limited as long as the total content of structural units derived from methyl methacrylate is 60 to 93% by mass, the total content of structural units derived from α-methylstyrene is 30 to 7% by mass, and the structural units derived from copolymerizable monomer (C) are 0 to 20% by mass. From the viewpoints of polymerizability, transparency, etc., the total content of structural units derived from methyl methacrylate in the precursor polymer is preferably 65% by mass or more and 93% by mass or less, more preferably 70% by mass or more and 92% by mass or less, and most preferably 75% by mass or more and 92% by mass or less.
[0055] From the viewpoints of heat resistance, polymerizability, water absorption, etc., the total content of structural units derived from α-methylstyrene in the precursor polymer is preferably 7% by mass or more and 30% by mass or less, more preferably 8% by mass or more and 27% by mass or less, and even more preferably 11 to 25% by mass. If the structural units derived from α-methylstyrene are less than this range, sufficient heat resistance cannot be obtained, and if they are more than this range, the polymerizability is significantly reduced. The total content of structural units derived from the copolymerizable monomer (C) in the precursor polymer is 0 to 20% by mass, preferably 0 to 15% by mass.
[0056] The precursor polymer has a polystyrene-equivalent weight average molecular weight Mw of preferably 30,000 to 200,000, more preferably 40,000 to 180,000, and even more preferably 50,000 to 160,000 in a chromatogram obtained by gel permeation chromatography. If the weight average molecular weight Mw is smaller than this range, the resulting molded article becomes brittle, and if it is higher than this range, the productivity deteriorates. Mw can be controlled by adjusting the type, amount, and addition timing of the polymerization initiator and chain transfer agent (optional components) used in the production of the precursor polymer.
[0057] The ring structure forming reaction can be carried out, for example, using an extruder. Examples of the extruder include a single screw extruder, a twin screw extruder, and a multi-screw extruder. From the viewpoint of mixing performance, a twin screw extruder is preferred. Twin screw extruders include non-intermeshing co-rotating type, intermeshing co-rotating type, non-intermeshing counter-rotating type, and intermeshing counter-rotating type. The intermeshing co-rotating type is preferred because it can rotate at high speed and can efficiently promote mixing. These extruders may be used alone or connected in series.
[0058] In the ring structure forming reaction using an extruder, for example, a precursor polymer as a raw material is charged from the raw material charging section of the extruder, the precursor polymer is melted, and the cylinder is filled with the precursor polymer. Then, an imidizing agent (optional component) and the like are injected into the extruder using an addition pump, whereby the ring structure forming reaction can be progressed in the extruder. When an imidizing agent is used, the structural unit (R) contains an N-substituted or unsubstituted glutarimide unit, and may contain a lactone ring unit and / or a glutaric anhydride unit as necessary. A preferred imidizing agent is R 2 -NH 2 (R 2 is as defined above). The imidizing agent is preferably used in an amount of 1.6 to 12 parts by mass per 100 parts by mass of the acrylic copolymer. When the amount of the imidizing agent used is within the above range, the by-production of methacrylic acid amide units can be suppressed.
[0059] The resin temperature in the reaction zone in the extruder is preferably in the range of 180 to 280°C, more preferably in the range of 200 to 280°C. If the resin temperature in the reaction zone is less than 180°C, the heat resistance of the acrylic copolymer tends to decrease due to a decrease in the reaction efficiency of the ring structure formation reaction, the by-production of methacrylic acid amide units, etc. If the resin temperature in the reaction zone exceeds 280°C, the resin decomposition becomes significant, and the mechanical strength, such as the tensile breaking strength, of the molded body and film made of the obtained acrylic copolymer tends to decrease. The reaction zone in the extruder refers to the region between the injection position of the imidizing agent, etc., in the cylinder of the extruder to the resin discharge port (die part).
[0060] By increasing the reaction time in the reaction zone of the extruder, the ring structure forming reaction can be promoted. The reaction time in the reaction zone of the extruder is preferably longer than 10 seconds, and more preferably longer than 30 seconds. If the reaction time is less than 10 seconds, the ring structure forming reaction may hardly proceed.
[0061] The resin pressure in the extruder is preferably in the range of atmospheric pressure to 50 MPa, and more preferably in the range of 1 to 30 MPa. If it is 50 MPa or more, it exceeds the limit of the mechanical pressure resistance of a normal extruder, and a special device is required, which is not preferable from the viewpoint of cost.
[0062] It is preferable to use an extruder having a vent hole that can reduce the pressure to below atmospheric pressure. With such a configuration, unreacted materials, by-products such as methanol, and monomers can be removed, and the breaking strength of a molded article containing the acrylic resin composition of the present invention tends to be improved.
[0063] For the ring structure-forming reaction, a horizontal twin-screw reactor such as Bivolac manufactured by Sumitomo Heavy Industries, Ltd. or a vertical twin-screw stirring tank such as Superblend, which is suitable for high viscosity reaction, can be suitably used instead of an extruder.
[0064] During the ring structure forming reaction, a carboxy group may be by-produced in the acrylic copolymer. This carboxy group may be converted to an ester group by an esterifying agent or a catalyst, if necessary. This can reduce foaming of the resin when producing an optical film. The ester group varies depending on the esterifying agent and catalyst used, but from the viewpoints of reducing the resin melt viscosity during melt molding, the reactivity of esterification, and the heat resistance of the resin after esterification, it is preferable that the ester group contains a methyl methacrylate unit, and more preferably contains both a methyl methacrylate unit and an ethyl methacrylate unit. As the esterifying agent, dimethyl carbonate is preferred from the viewpoints of cost, reactivity, etc.
[0065] (Elastomer (B)) The content of the elastomer (B) in the acrylic resin composition of the present invention is 1 to 49 mass%, preferably 5 to 45 mass%, and more preferably 10 to 40 mass%. The brittleness of the acrylic resin composition of the present invention is improved by having the content of the elastomer (B) in the range of 1 to 49 mass%.
[0066] The elastomer (B) used in the present invention is not particularly limited as long as it can be kneaded with the acrylic copolymer (A) to obtain a resin composition. The elastomer (B) is preferably one that forms a dispersed phase in the resin composition. The form of the dispersed phase is not particularly limited, and examples thereof include spherical, ellipsoidal, rod-like, flat, and string-like.
[0067] The elastomer (B) preferably has an acrylate unit. Examples of the acrylate include alkyl acrylates such as methyl acrylate, ethyl acrylate, and butyl acrylate; aryl acrylates such as phenyl acrylate and benzyl acrylate; and cycloalkyl acrylates such as cyclohexyl acrylate and norbornenyl acrylate. Among these, alkyl acrylates are preferred, and butyl acrylate is the most preferred. The amount of acrylic ester units contained in the elastomer (B) is preferably 30% by mass or more, more preferably from 35% by mass to 90% by mass or less, and further preferably from 40% by mass to 80% by mass or less.
[0068] The elastomer (B) may have a vinyl monomer unit having only one polymerizable carbon-carbon double bond in one molecule in addition to the acrylic ester unit. Examples of the vinyl monomer include methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, and 2-ethylhexyl methacrylate; methacrylic acid aryl esters such as phenyl methacrylate; methacrylic acid cycloalkyl esters such as cyclohexyl methacrylate and norbornenyl methacrylate; aromatic vinyl compounds such as styrene and α-methylstyrene; acrylamide; methacrylamide; acrylonitrile; and methacrylonitrile.
[0069] The elastomer (B) may have a vinyl monomer unit having only one polymerizable carbon-carbon double bond in one molecule in addition to the acrylic ester unit. Examples of the vinyl monomer include methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, and 2-ethylhexyl methacrylate; methacrylic acid aryl esters such as phenyl methacrylate; methacrylic acid cycloalkyl esters such as cyclohexyl methacrylate and norbornenyl methacrylate; aromatic vinyl compounds such as styrene and α-methylstyrene; acrylamide; methacrylamide; acrylonitrile; and methacrylonitrile.
[0070] The elastomer (B) may further contain conjugated diene monomer units, such as those containing 1,3-butadiene, isoprene, or both of these units.
[0071] The elastomer (B) is not particularly limited by its molecular form, and examples thereof include linear polymer elastomers, branched polymer elastomers, multilayer copolymer elastomers, and block copolymer elastomers. Of these, the elastomer (B) is preferably one containing a multilayer copolymer elastomer having methacrylic acid ester units and acrylic acid ester units, or one containing a block copolymer elastomer consisting of a polymer block (b1) mainly having methacrylic acid ester units and a polymer block (b2) having acrylic acid ester units. The elastomer (B) may contain a combination of a block copolymer elastomer and a multilayer copolymer elastomer.
[0072] The multilayer copolymer elastomer may be one that is composed of an outermost layer made of a thermoplastic polymer (P) and an inner layer made of a crosslinked polymer that is in contact with and covers the outermost layer, and it is preferable that the inner layer and the outermost layer form a core and a shell. For example, the multilayer copolymer elastomer may be a two-layer polymer elastomer having a core (inner layer) of a crosslinked rubber polymer (Q) and an outer shell (outermost layer) of a thermoplastic polymer (P), a three-layer polymer elastomer having a core (inner layer) of a crosslinked polymer (R), an inner shell (inner layer) of a crosslinked rubber polymer (Q) and an outer shell (outermost layer) of a thermoplastic polymer (P), or a four-layer polymer elastomer having a core (inner layer) of a crosslinked rubber polymer (Q), a first inner shell (inner layer) of a crosslinked polymer (R), a second inner shell (inner layer) of a crosslinked rubber polymer (Q) and an outer shell (outermost layer) of a thermoplastic polymer (P).
[0073] From the viewpoint of transparency, it is preferable to select the polymers contained in each layer so that the difference in refractive index between adjacent layers is preferably less than 0.005, more preferably less than 0.004, and even more preferably less than 0.003.
[0074] The mass ratio of the inner layer to the outermost layer in the multilayer copolymer elastomer is preferably 60 / 40 to 95 / 5, more preferably 70 / 30 to 90 / 10. The proportion of the layer containing the crosslinked rubber polymer (Q) in the inner layer is preferably 20 to 70 mass%, more preferably 30 to 50 mass%.
[0075] The multilayer copolymer elastomer has an average particle size of preferably 0.05 to 3 μm, more preferably 0.1 to 2 μm, and even more preferably 0.2 to 1 μm. When a multilayer copolymer elastomer having an average particle size within such a range, particularly an average particle size of 0.2 to 1 μm, is used, toughness can be exhibited even with a small amount of the elastomer, and therefore rigidity and surface hardness are not impaired. In this specification, the average particle size is the average value in the volume-based particle size distribution measured by a light scattering method.
[0076] The thermoplastic polymer (P) is a polymer comprising methacrylic acid alkyl ester units having an alkyl group having 1 to 8 carbon atoms and, if necessary, monofunctional monomer units other than the methacrylic acid alkyl esters. It is preferable that the thermoplastic polymer (P) does not contain polyfunctional monomer units.
[0077] The amount of the methacrylic acid alkyl ester units having an alkyl group having 1 to 8 carbon atoms constituting the thermoplastic polymer (P) is preferably 80 to 100 mass %, more preferably 85 to 95 mass %, based on the mass of the thermoplastic polymer (P).
[0078] As the methacrylic acid alkyl ester having an alkyl group having 1 to 8 carbon atoms (hereinafter, sometimes referred to as methacrylic acid C1-8 alkyl ester), for example, methyl methacrylate is preferable.
[0079] The amount of monofunctional monomer units other than C1-8 alkyl methacrylate constituting the thermoplastic polymer (P) is preferably 0 to 20 mass %, more preferably 5 to 15 mass %, based on the mass of the thermoplastic polymer (P). Examples of monofunctional monomers other than methacrylic acid C1-8 alkyl esters include acrylic esters such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and propyl acrylate; and aromatic vinyl compounds such as styrene.
[0080] The outermost layer may be a single layer made of one kind of thermoplastic polymer (P), or may be a multilayer made of two or more kinds of thermoplastic polymers (P).
[0081] The amount of the thermoplastic polymer (P) is preferably 40 to 75% by mass, more preferably 45 to 70% by mass, and further preferably 50 to 65% by mass, based on the amount of the multilayer copolymer elastomer.
[0082] The layer of crosslinked elastic material which is the inner layer has an intermediate layer made of a crosslinked rubber polymer (Q) and an inner layer made of a crosslinked polymer (R) which is in contact with and covers the intermediate layer.
[0083] The crosslinked polymer (R) is composed of methyl methacrylate units, monofunctional monomer units other than methyl methacrylate, and polyfunctional monomer units.
[0084] The amount of methyl methacrylate units constituting the crosslinked polymer (R) is preferably 40 to 98.5% by mass, more preferably 45 to 95% by mass, based on the mass of the crosslinked polymer (R).
[0085] The amount of the monofunctional monomer units other than methyl methacrylate constituting the crosslinked polymer (R) is 1 to 59.5% by mass, preferably 5 to 55% by mass, based on the mass of the crosslinked polymer (R). Examples of monofunctional monomers other than methyl methacrylate include acrylic esters such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and propyl acrylate; and aromatic vinyl compounds such as styrene.
[0086] The amount of the polyfunctional monomer unit constituting the crosslinked polymer (R) is preferably 0.05 to 0.4 mass %, more preferably 0.1 to 0.3 mass %, based on the mass of the crosslinked polymer (R). Examples of the polyfunctional monomer include ethylene glycol dimethacrylate, propylene glycol dimethacrylate, triethylene glycol dimethacrylate, hexanediol dimethacrylate, ethylene glycol diacrylate, propylene glycol diacrylate, triethylene glycol diacrylate, allyl methacrylate, and triallyl isocyanurate.
[0087] The amount of the crosslinked polymer (R) is preferably 5 to 40% by mass, more preferably 7 to 35% by mass, and further preferably 10 to 30% by mass, based on the amount of the multilayer copolymer elastomer.
[0088] The crosslinked rubber polymer (Q) comprises acrylate alkyl ester units having an alkyl group having 1 to 8 carbon atoms and / or conjugated diene units, and polyfunctional monomer units.
[0089] The amount of the acrylic acid alkyl ester units and / or conjugated diene units having an alkyl group having 1 to 8 carbon atoms constituting the crosslinked rubber polymer (Q) is preferably 85 to 99 mass %, more preferably 95 to 98 mass %, based on the mass of the crosslinked rubber polymer (Q).
[0090] Examples of the alkyl acrylate ester having an alkyl group having 1 to 8 carbon atoms include methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and propyl acrylate.
[0091] Examples of conjugated dienes include 1,3-butadiene and isoprene.
[0092] Examples of the crosslinked rubber polymer (Q) containing 1,3-butadiene as a monomer include 1,3-polybutadiene homopolymers and copolymers composed of 50% by weight or more of 1,3-polybutadiene units. Examples of such copolymers include butadiene-aromatic vinyl compound copolymers such as butadiene-styrene copolymers and butadiene-vinyltoluene copolymers, and further include terpolymers composed of 50% by weight or more of 1,3-butadiene units. These can usually be easily produced by known emulsion polymerization.
[0093] The amount of the polyfunctional monomer unit constituting the crosslinked rubber polymer (Q) is preferably 1 to 1.7 mass %, more preferably 1.2 to 1.6 mass %, and further preferably 1.3 to 1.5 mass %, based on the mass of the crosslinked rubber polymer (Q). As the polyfunctional monomer, those exemplified for the crosslinked polymer (R) can be mentioned.
[0094] From the viewpoint of improving flex resistance, the ratio of the mass of the polyfunctional monomer unit in the crosslinked polymer (R) to the mass of the polyfunctional monomer unit in the crosslinked rubber polymer (Q) is preferably 0.05 to 0.25, more preferably 0.1 to 0.2. The glass transition temperature of the crosslinked rubber polymer (Q) is preferably lower than the glass transition temperature of the crosslinked polymer (R).
[0095] The amount of the crosslinked rubber polymer (Q) is preferably 20 to 55% by mass, more preferably 25 to 45% by mass, and further preferably 30 to 40% by mass, based on the amount of the multilayer copolymer elastomer.
[0096] The multilayer copolymer elastomer has an average diameter (d) of the crosslinked elastic layer of preferably 60 to 110 nm, more preferably 65 to 105 nm, and even more preferably 70 to 100 nm. The average diameter d (nm) of the crosslinked elastic layer can be measured as follows. A resin composition containing the multilayer copolymer elastomer is molded using a hydraulic press molding machine with a mold size of 50 mm x 120 mm, a press temperature of 250°C, a preheating time of 3 minutes, and a press pressure of 50 kg / cm. 2, press time 30 seconds, cooling temperature 20℃, cooling pressure 50kg / cm 2 The plate is molded into a 3 m plate under the conditions of 10 minutes cooling time. The plate obtained is cut in a direction parallel to the long side at -100°C using a microtome to obtain a 40 nm thick slice, which is then stained with ruthenium. The stained slice is observed and photographed using a scanning transmission electron microscope (JEOL JSM7600F) at an accelerating voltage of 25 kV. The short and long diameters of the ruthenium-stained portion (exposed portion of the cross-linked elastic layer) are measured, and (short diameter + long diameter) / 2 is defined as the diameter of the cross-linked elastic layer. After measuring 20 or more pieces, the number average value (average diameter) is calculated.
[0097] The multi-layer copolymer elastomer may be produced by any method, including, for example, emulsion polymerization. In the case of emulsion polymerization, for example, a monomer (r) for constituting a crosslinked polymer (R) is emulsion-polymerized to obtain a latex containing the crosslinked polymer (R), a monomer (q) for constituting a crosslinked rubber polymer (Q) is added thereto, and the monomer (q) is seed-emulsion-polymerized to obtain a latex containing the crosslinked polymer (R) and the crosslinked rubber polymer (q), and a monomer (p) for constituting a thermoplastic polymer (P) is added thereto, and the monomer (p) is seed-emulsion-polymerized to obtain a latex containing a multilayer copolymer elastomer. Incidentally, emulsion polymerization is a known method used to obtain a latex containing a polymer. Seed emulsion polymerization is a method in which a polymerization reaction of a monomer is carried out on the surface of a seed particle. Seed emulsion polymerization is preferably used to obtain a core-shell structure polymer particle.
[0098] The block copolymer elastomer preferably comprises a polymer block (b1) mainly having methacrylic acid ester units and a polymer block (b2) having acrylic acid ester units. The block copolymer elastomer may have only one polymer block (b1) in one molecule, or may have multiple polymer blocks (b1). Also, the block copolymer elastomer may have only one polymer block (b2) in one molecule, or may have multiple polymer blocks (b2).
[0099] The amount of methacrylic acid ester units contained in the polymer block (b1) is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 98% by mass or more. As the methacrylic acid ester, for example, methyl methacrylate is preferable. The methacrylic acid ester can be used alone or in combination of two or more kinds in the polymer block (b1).
[0100] The amount of polymer block (b1) contained in the block copolymer elastomer is preferably from 40% by mass to 90% by mass, more preferably from 45% by mass to 80% by mass, from the viewpoints of transparency, flexibility, bending resistance, impact resistance, softness, moldability, surface smoothness, etc.
[0101] The glass transition temperature of the polymer block (b2) is preferably 20° C. or lower, more preferably −20° C. or lower.
[0102] The amount of acrylic acid ester units contained in the polymer block (b2) is preferably 90% by mass or more. Examples of acrylic acid esters include n-butyl acrylate and benzyl acrylate. These acrylic acid esters can be used alone or in combination of two or more in the polymer block (b2).
[0103] The polymer block (b2) may contain a monomer unit other than an acrylic ester, so long as it does not impede the object and effect of the present invention.
[0104] The polymer block (b2) preferably comprises an acrylic acid alkyl ester unit and a (meth)acrylic acid aromatic ester unit from the viewpoint of transparency, etc. The mass ratio of the acrylic acid alkyl ester unit / the (meth)acrylic acid aromatic ester unit is preferably 50 / 50 to 90 / 10, more preferably 60 / 40 to 80 / 20.
[0105] The bonding form between the polymer block (b1) and the polymer block (b2) contained in the block copolymer elastomer is not particularly limited. For example, a copolymer in which one end of the polymer block (b2) is bonded to one end of the polymer block (b1) (b1-b2 diblock copolymer) or a copolymer in which one end of the polymer block (b1) is bonded to each of both ends of the polymer block (b2) (b1-b2-b1 triblock copolymer) is preferred.
[0106] The block copolymer elastomer has a weight average molecular weight of preferably 52,000 to 400,000, more preferably 60,000 to 300,000. The block copolymer elastomer also has a ratio of the weight average molecular weight to the number average molecular weight of preferably 1.01 to 2.00, more preferably 1.05 to 1.60. The weight average molecular weight and number average molecular weight of the block copolymer elastomer can be appropriately set from the viewpoints of moldability, tensile strength, appearance, etc. The weight average molecular weight and number average molecular weight are values measured by GPC (gel permeation chromatography) in terms of standard polystyrene.
[0107] The block copolymer elastomer is not particularly limited by its manufacturing method, and can be obtained by a known method. For example, a method including living polymerization of monomers constituting each polymer block is generally used. As the living polymerization method, a method including anionic polymerization in the presence of an organic alkali metal compound and an organic aluminum compound is preferred, since it can obtain a high-purity block copolymer elastomer, and it is easy to control the molecular weight and composition ratio, and it is inexpensive.
[0108] (Acrylic resin composition) In the acrylic resin composition of the present invention, the mass ratio of the acrylic copolymer (A) / the elastomer (B) is from 99 / 1 to 51 / 49, preferably from 95 / 5 to 55 / 45, and more preferably from 90 / 10 to 60 / 40, from the viewpoints of impact resistance and surface hardness.
[0109] The acrylic resin composition of the present invention has a melt flow rate at 230° C. under a load of 3.8 kg of preferably 1 g / 10 min or more, more preferably 1.5 to 35 g / 10 min, and further preferably 2 to 20 g / 10 min. The melt flow rate is a melt mass flow rate value measured in accordance with JIS K7210.
[0110] The acrylic resin composition of the present invention has a glass transition temperature of preferably 100 to 160° C., more preferably 105 to 155° C., and further preferably 110 to 150° C. If the glass transition temperature is 100° C. or lower, the heat resistance and the like tend to decrease, and if the glass transition temperature is 160° C. or higher, the moldability and the like tend to decrease.
[0111] The acrylic resin composition of the present invention has a softening temperature of a molded product measured by the method specified in JIS K7206 B50 method of preferably 110° C. or higher, more preferably 115° C. or higher, and even more preferably 120° C. or higher. When the softening temperature is 110° C. or higher, the molded product has excellent heat resistance and excellent dimensional stability at high temperatures.
[0112] The acrylic resin composition of the present invention has a saturated water absorption of 2.5% or less, more preferably 2.1% or less, and even more preferably 2.0% or less, measured under the same conditions as those for measuring the saturated water absorption of the acrylic copolymer (A). The saturated water absorption of 2.5% or less provides excellent dimensional stability under high humidity conditions.
[0113] The acrylic resin composition of the present invention may contain a filler as necessary within a range that does not impair the effects of the present invention. Examples of the filler include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate, magnesium carbonate, etc. The amount of the filler that can be contained in the resin composition of the present invention is preferably 3 mass % or less, more preferably 1.5 mass % or less.
[0114] The acrylic resin composition of the present invention may contain other polymers as long as the effects of the present invention are not impaired. Examples of other polymers include polyolefin resins such as polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; ethylene-based ionomers; styrene-based resins such as polystyrene, styrene-maleic anhydride copolymer, high impact polystyrene, AS resin, ABS resin, AES resin, AAS resin, ACS resin, and MBS resin; methyl methacrylate-based polymers other than the acrylic copolymer (A), and methyl methacrylate-styrene copolymers; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyamides such as nylon 6, nylon 66, and polyamide elastomers; polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polyacetal, polyvinylidene fluoride, polyurethane, phenoxy resins, modified polyphenylene ethers, polyphenylene sulfide, and silicone-modified resins; silicone rubber; styrene-based thermoplastic elastomers such as SEPS, SEBS, and SIS; and olefin-based rubbers such as IR, EPR, and EPDM. The amount of other polymers that can be contained in the resin composition of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, and most preferably 0% by mass.
[0115] The acrylic resin composition of the present invention may contain additives such as antioxidants, heat deterioration inhibitors, ultraviolet absorbers, light stabilizers, lubricants, release agents, polymer processing aids, antistatic agents, flame retardants, dyes and pigments, light diffusing agents, organic dyes, matting agents, and fluorescent materials, as long as the effects of the present invention are not impaired.
[0116] The antioxidant is effective in preventing the oxidative deterioration of the resin by itself in the presence of oxygen. Examples of the antioxidant include phosphorus-based antioxidants, hindered phenol-based antioxidants, and thioether-based antioxidants. These antioxidants can be used alone or in combination of two or more. Among these, from the viewpoint of the effect of preventing the deterioration of optical properties due to coloring, phosphorus-based antioxidants and hindered phenol-based antioxidants are preferred, and the combined use of a phosphorus-based antioxidant and a hindered phenol-based antioxidant is more preferred. When the phosphorus-based antioxidant and the hindered phenol-based antioxidant are used in combination, their ratio is not particularly limited, but the mass ratio of the phosphorus-based antioxidant / the hindered phenol-based antioxidant is preferably 1 / 5 to 2 / 1, and more preferably 1 / 2 to 1 / 1.
[0117] Examples of phosphorus-based antioxidants include 2,2-methylenebis(4,6-di-t-butylphenyl)octyl phosphite (manufactured by ADEKA Corporation; trade name: Adeka STAB HP-10), tris(2,4-di-t-butylphenyl)phosphite (manufactured by Ciba Specialty Chemicals Corporation; trade name: IRUGA FOS 168), and 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (manufactured by ADEKA Corporation; trade name: Adeka STAB PEP-36).
[0118] Examples of the hindered phenol antioxidant include pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (manufactured by Ciba Specialty Chemicals; trade name IRGANOX1010) and octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (manufactured by Ciba Specialty Chemicals; trade name IRGANOX1076).
[0119] The thermal degradation inhibitor is a compound that can prevent thermal degradation of a resin by capturing polymer radicals that are generated when the resin is exposed to high heat in a substantially oxygen-free state. Examples of the thermal degradation inhibitor include 2-t-butyl-6-(3'-t-butyl-5'-methyl-hydroxybenzyl)-4-methylphenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GM) and 2,4-di-t-amyl-6-(3',5'-di-t-amyl-2'-hydroxy-α-methylbenzyl)phenyl acrylate (manufactured by Sumitomo Chemical Co., Ltd.; product name: Sumilizer GS).
[0120] An ultraviolet absorber is a compound that has the ability to absorb ultraviolet rays. An ultraviolet absorber is a compound that is said to have the function of converting light energy into heat energy. Examples of ultraviolet absorbents include benzophenones, benzotriazoles, triazines, benzoates, salicylates, cyanoacrylates, oxalic anilides, malonic acid esters, and formamidines. These may be used alone or in combination of two or more. Among these, benzotriazoles, triazines, or compounds having a maximum molar absorption coefficient εmax of 1200 dm at a wavelength of 380 to 450 nm are particularly preferred. 3 Mol -1 cm -1 Preferred are UV absorbers which are:
[0121] As the benzotriazoles, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (manufactured by BASF; trade name TINUVIN329), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (manufactured by BASF; trade name TINUVIN234), 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol] (manufactured by ADEKA; trade name LA-31), 2-(5-octylthio-2H-benzotriazol-2-yl)-6-tert-butyl-4-methylphenol, and the like are preferred.
[0122] In addition, when it is desired to efficiently absorb short wavelengths of 380 nm or less, triazine ultraviolet absorbers are preferably used. Examples of such ultraviolet absorbers include 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine (manufactured by ADEKA; product name LA-F70), its analogues, hydroxyphenyltriazine ultraviolet absorbers (manufactured by BASF; product names TINUVIN477, TINUVIN460, and TINUVIN479), and 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine.
[0123] The maximum molar absorption coefficient εmax of the ultraviolet absorber is measured as follows. 10.00 mg of ultraviolet absorber is added to 1 L of cyclohexane, and dissolved until no undissolved matter is found by visual observation. This solution is poured into a quartz glass cell measuring 1 cm x 1 cm x 3 cm, and the absorbance at wavelengths of 380 to 450 nm is measured using a spectrophotometer (Hitachi, Ltd.; product name U-3410). The maximum molar absorption coefficient εmax is calculated from the molecular weight (MUV) of the ultraviolet absorber and the maximum absorbance (Amax) measured using the following formula. εmax = [Amax / (10 × 10 -3 )]×MUV
[0124] Light stabilizers are compounds that are said to have the function of capturing radicals generated mainly by oxidation due to light, and examples thereof include hindered amines such as compounds having a 2,2,6,6-tetraalkylpiperidine skeleton.
[0125] Examples of the lubricant include stearic acid, behenic acid, stearamide acid, methylene bisstearamide, hydroxystearic acid triglyceride, paraffin wax, ketone wax, octyl alcohol, and hardened oil.
[0126] The mold release agent is a compound having a function of facilitating the release of a molded product from a mold, and examples thereof include higher alcohols such as cetyl alcohol and stearyl alcohol, and higher fatty acid esters of glycerin such as monoglyceride stearate and diglyceride stearate. The use of higher fatty acid esters of glycerin may cause gel-like foreign matter, so it is preferable to use higher alcohols.
[0127] The polymer processing aid is a compound that is effective in achieving thickness accuracy and thinning when molding an acrylic resin composition. The polymer processing aid can usually be produced by an emulsion polymerization method. The polymer processing aid is preferably a polymer particle having a particle size of 0.05 to 0.5 μm. The polymer particles may be single-layer particles made of a polymer with a single composition ratio and a single intrinsic viscosity, or may be multi-layer particles made of two or more polymers with different composition ratios or intrinsic viscosities. Among these, preferred are particles with a two-layer structure having a polymer layer with a low intrinsic viscosity in the inner layer and a polymer layer with a high intrinsic viscosity of 5 dl / g or more in the outer layer. The polymer processing aid preferably has an intrinsic viscosity of 3 to 6 dl / g. If the intrinsic viscosity is too low, the effect of improving moldability is low. If the intrinsic viscosity is too high, the melt flowability of the acrylic resin composition is likely to decrease.
[0128] Examples of the antistatic agent include alkylsulfonates such as sodium heptyl sulfonate, sodium octyl sulfonate, sodium nonyl sulfonate, sodium decyl sulfonate, sodium dodecyl sulfonate, sodium cetyl sulfonate, sodium octadecyl sulfonate, sodium diheptyl sulfonate, potassium heptyl sulfonate, potassium octyl sulfonate, potassium nonyl sulfonate, potassium decyl sulfonate, potassium dodecyl sulfonate, potassium cetyl sulfonate, potassium octadecyl sulfonate, potassium diheptyl sulfonate, lithium heptyl sulfonate, lithium octyl sulfonate, lithium nonyl sulfonate, lithium decyl sulfonate, lithium dodecyl sulfonate, lithium cetyl sulfonate, lithium octadecyl sulfonate, and lithium diheptyl sulfonate.
[0129] Examples of the flame retardant include metal hydrates having a hydroxyl group or crystal water, such as magnesium hydroxide, aluminum hydroxide, hydrated aluminum silicate, hydrated magnesium silicate, and hydrotalcite; phosphate compounds, such as polyamine phosphoric acid esters; and silicon compounds. Of these, preferred are phosphate ester-based flame retardants, such as trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, dimethylethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, and hydroxyphenyl diphenyl phosphate.
[0130] Examples of dyes and pigments include red organic pigments such as Para Red, Fire Red, Pyrazolone Red, Thioindigo Red, and Perylene Red; blue organic pigments such as Cyanine Blue and Indanthrene Blue; and green organic pigments such as Cyanine Green and Naphthol Green. One or more of these can be used.
[0131] As the organic dye, a compound having a function of converting ultraviolet light into visible light is preferably used. Examples of the light diffusing agent and the matting agent include glass particles, polysiloxane-based crosslinked particles, crosslinked polymer particles, talc, calcium carbonate, and barium sulfate. Examples of fluorescent materials include fluorescent pigments, fluorescent dyes, fluorescent white dyes, fluorescent brighteners, and fluorescent bleaches.
[0132] These additives may be used alone or in combination of two or more. These additives may be added to the polymerization reaction solution when producing the acrylic copolymer (A) and the elastomer (B), or may be added to the produced acrylic copolymer (A) and the crosslinked rubber (B), or may be added when preparing the acrylic resin composition of the present invention. The total amount of additives contained in the acrylic resin composition of the present invention is preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less, based on the acrylic resin composition, from the viewpoint of suppressing defective appearance of the molded product.
[0133] The method for preparing the acrylic resin composition of the present invention is not particularly limited. For example, a method of polymerizing a monomer mixture containing methyl methacrylate or the like in the presence of an elastomer (B) to produce an acrylic copolymer (A), or a method of melt-kneading the acrylic copolymer (A) and the elastomer (B) can be mentioned. During melt-kneading, other polymers and additives may be mixed as necessary, the acrylic copolymer (A) may be mixed with other polymers and additives and then mixed with the elastomer (B), the elastomer (B) may be mixed with other polymers and additives and then mixed with the acrylic copolymer (A), or other methods may be used. Kneading can be performed using a known mixing or kneading device such as a kneader-ruder, an extruder, a mixing roll, or a Banbury mixer. Of these, a twin-screw extruder is preferred.
[0134] The acrylic resin composition of the present invention can be made into a form such as pellets in order to enhance convenience during storage, transportation, or molding.
[0135] The molded article of the present invention is made of the acrylic resin composition of the present invention. The manufacturing method of the molded article of the present invention is not particularly limited. For example, melt molding methods such as the T-die method (lamination method, co-extrusion method, etc.), inflation method (co-extrusion method, etc.), compression molding method, blow molding method, calendar molding method, vacuum molding method, injection molding method (insert method, two-color method, press method, core-back method, sandwich method, etc.), and solution casting method can be mentioned. Among these, the T-die method, inflation method, and injection molding method are preferred from the viewpoint of high productivity, cost, etc. There is no limitation on the type of molded article, but films (planar molded articles having a thickness of 5 μm to 250 μm) and sheets (planar molded articles thicker than 250 μm) are preferred, and among them, films are particularly preferred.
[0136] The film, which is one form of the molded article of the present invention, can be produced by a solution casting method, a melt casting method, an extrusion molding method, an inflation molding method, a blow molding method, etc. Among these, the extrusion molding method is preferred from the viewpoint of obtaining a film having excellent transparency, improved toughness, excellent handling properties, and an excellent balance between toughness, surface hardness, and rigidity. The temperature of the molten resin discharged from the extruder is preferably set to 160 to 270°C, more preferably 220 to 260°C.
[0137] Among the extrusion molding methods, the T-die method is preferred from the viewpoint of obtaining a film with good surface smoothness, good mirror gloss, and low haze. In this T-die method, it is preferable to sandwich the molten resin discharged from the T-die through an extruder, a gear pump, a polymer filter, and a mixer between two or more mirror-finished rolls or mirror-finished belts to form a film. When sandwiching between the mirror-finished rolls or mirror-finished belts, a bank may or may not be formed. The die has an automatic lip opening adjustment function, and the air gap is preferably 100 mm or less. The mirror-finished roll or mirror-finished belt is preferably made of metal. As the mirror-finished roll, a metal rigid roll, a metal elastic roll, etc. can be used, and it is preferable to use a combination of a metal elastic roll and a metal rigid roll. In addition, the surface temperatures of both the mirror-finished roll or the mirror-finished belt are preferably 130°C or less. In addition, it is preferable that at least one of the pair of mirror-finished rolls or mirror-finished belts has a surface temperature of 60°C or more. By setting the surface temperature at such a level, the molten resin discharged from the extruder can be cooled at a rate faster than natural cooling, and a film with excellent surface smoothness and low haze can be easily produced. The linear pressure between the pair of rolls or belts is preferably 10 N / mm or more, more preferably 30 N / mm or more. The thickness of the unstretched film obtained by extrusion molding is preferably 10 to 300 μm. The haze of the film at a thickness of 100 μm is preferably 0.57% or less, more preferably 0.35% or less, and even more preferably 0.3% or less.
[0138] The unstretched film obtained as described above may be subjected to a stretching treatment. The stretching treatment increases the mechanical strength, and a film that is less likely to crack can be obtained. The stretching method is not particularly limited, and examples thereof include simultaneous biaxial stretching, sequential biaxial stretching, and tubular stretching. From the viewpoint of obtaining a film that can be uniformly stretched and has high strength, the lower limit of the temperature during stretching is a temperature 10°C higher than the glass transition temperature of the acrylic copolymer or acrylic resin composition, and the upper limit of the temperature during stretching is a temperature 40°C higher than the glass transition temperature of the acrylic copolymer or acrylic resin composition. The stretching is usually performed at 100 to 5000% / min. After the stretching, a film with little thermal shrinkage can be obtained by performing heat setting. The thickness of the film after stretching is preferably 10 to 200 μm.
[0139] A functional layer may be provided on the surface of the film, which is one embodiment of the molded article of the present invention. Examples of the functional layer include a hard coat layer, an antiglare layer, an antireflection layer, an antisticking layer, a diffusion layer, an antiglare layer, an antistatic layer, an antifouling layer, and a slippery layer such as a fine particle layer.
[0140] In addition, it is preferable to provide an undercoat layer on at least one side of the film of the present invention in order to improve the adhesive strength with the functional layer or to improve the adhesive strength when laminated with other films via an adhesive or pressure-sensitive adhesive.
[0141] The acrylic resin composition of the present invention is suitable as a molding material. The molded article of the present invention can be used as a member for various applications. Specific applications include, for example, signboard parts and marking films such as advertising towers, stand signs, side signs, transom signs, and rooftop signs; display parts such as showcases, partitions, and store displays; lighting parts such as fluorescent lamp covers, mood lighting covers, lampshades, light ceilings, light walls, and chandeliers; interior parts such as furniture, pendants, and mirrors; architectural parts such as doors, domes, safety window glass, partitions, staircase wainscoting, balcony wainscoting, and roofs of leisure buildings; transportation-related parts such as aircraft windshields, pilot visors, motorcycle and motorboat windshields, bus shading plates, automobile side visors, rear visors, head wings, headlight covers, automobile interior parts, and automobile exterior parts such as bumpers; audiovisual nameplates, stereo covers, tapes, etc. Examples of applications include electronic equipment parts such as Levi's protective masks, vending machines, mobile phones, and personal computers; medical equipment parts such as incubators and X-ray parts; equipment-related parts such as machine covers, instrument covers, experimental equipment, rulers, dials, and observation windows; optical parts such as liquid crystal protection plates, light guide plates, light guide films, Fresnel lenses, lenticular lenses, front panels of various displays, and diffusion plates; traffic-related parts such as road signs, information boards, curved mirrors, and soundproof walls; and other parts for greenhouses, large aquariums, box aquariums, bathroom components, clock panels, bathtubs, sanitary products, desk mats, game parts, toys, musical instruments, face protection masks during welding, back sheets for solar cells, front sheets for flexible solar cells, and decorative films.
[0142] A laminate can be obtained by laminating a layer containing the acrylic resin composition of the present invention with another material (for example, a layer containing another thermoplastic copolymer). Examples of other materials used in the laminate include steel, plastic (for example, thermoplastic resin), wood, glass, etc. The laminate obtained by the present invention can be suitably used for wallpaper; automobile interior surface; automobile exterior surface such as bumper; mobile phone surface; furniture surface; personal computer surface; vending machine surface; bathroom surface such as bathtub, etc.
[0143] The film, which is one embodiment of the molded article of the present invention, is highly transparent and heat resistant, and therefore suitable for optical applications, and is particularly suitable for polarizer protection films, liquid crystal protection plates, surface materials for portable information terminals, display window protection films for portable information terminals, light guiding films, transparent conductive films with silver nanowires or carbon nanotubes applied to the surface, and front panels for various displays. The film of the present invention has high transparency and heat resistance, and can be used for applications other than optical applications, such as infrared cut films, crime prevention films, shatterproof films, decorative films, metal decorative films, shrink films, and in-mold label films.
[0144] When the film, which is one embodiment of the molded article of the present invention, is used as a polarizer protective film or a retardation film, it may be laminated on only one side of the polarizer film or on both sides. When laminating with the polarizer film, it can be laminated via an adhesive layer or a pressure-sensitive adhesive layer. As the polarizer film, a stretched film made of a polyvinyl alcohol resin and iodine can be used, and its thickness is preferably 1 to 100 μm. EXAMPLES
[0145] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0146] Measurements of physical properties were carried out by the following methods.
[0147] (Weight average molecular weight) The weight average molecular weight (Mw) of the resin obtained in the manufacturing example was determined by the GPC method (gas chromatography method). 4 mg of the resin to be measured was dissolved in 5 ml of tetrahydrofuran to prepare a sample solution. The temperature of the column oven was set to 40°C, and 20 μl of the sample solution was injected into the device at an eluent flow rate of 0.35 ml / min to measure the chromatogram. Ten standard polystyrene points with molecular weights in the range of 400 to 5,000,000 were measured by GPC, and a calibration curve showing the relationship between retention time and molecular weight was created. The Mw of the resin to be measured was determined based on this calibration curve. The value equivalent to the molecular weight of the standard polystyrene from the chromatogram measured by GPC (gel permeation chromatography) was taken as the molecular weight of the copolymer. Equipment: Tosoh GPC equipment HLC-8320 Separation column: Tosoh Corporation's TSKguardcolum SuperHZ-H, TSKgel HZM-M, and TSKgel SuperHZ4000 connected in series Eluent: Tetrahydrofuran Eluent flow rate: 0.35 ml / min Column temperature: 40℃ Detection method: Refractive index (RI)
[0148] (Composition of each unit in the copolymer) 13 The carbon ratio of the phenyl group of the α-methylstyrene unit, the carbonyl group of the methyl methacrylate unit, and the phenyl group of the styrene unit was determined by C-NMR, and the composition of each unit was calculated based on this.
[0149] (glass transition temperature Tg) The resin obtained in the Production Examples was measured for its DSC curve in accordance with JIS K7121 using a differential scanning calorimeter (Shimadzu Corporation, DSC-50 (product number)) by heating it once to 250° C., then cooling it to room temperature, and then heating it from room temperature to 200° C. at a rate of 10° C. / min. The midpoint glass transition temperature determined from the DSC curve measured during the second heating was taken as the glass transition temperature in the present invention.
[0150] (Unit composition of acrylic copolymer) The α-methylstyrene units and styrene units had the same composition as those of the precursor polymer. 1 Using H-NMR (Bruker Corporation; product name ULTRA SHIELD 400 PLUS), the acrylic copolymer 1 H-NMR measurement was performed to determine the content (mol%) of each monomer unit in the acrylic copolymer, such as glutarimide units, methyl methacrylate units, and aromatic vinyl (α-methylstyrene and styrene) units, and the content (mol%) was converted to the content (weight%) using the molecular weight of each monomer unit.
[0151] (1% thermogravimetric reduction temperature) The acrylic copolymers obtained in the Production Examples and the acrylic resin compositions obtained in the Examples and Comparative Examples were heated at a rate of 10°C / min in a nitrogen atmosphere using a thermogravimetric analyzer (Shimadzu Corporation, TGA-50), and the temperature at which a 1% weight loss occurred was recorded as the 1% thermal weight loss temperature.
[0152] (Vicat softening temperature) The acrylic resin compositions obtained in the Examples and Comparative Examples were injection molded using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.) under conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain rectangular test pieces with a thickness of 4 mm, a long side of 80 mm, and a short side of 10 mm. The Vicat softening temperature (VST) of each test piece was measured using an HDT tester 3M-2 manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with the method described in the B50 method of JIS K7206.
[0153] (Flexural modulus) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the acrylic copolymers obtained in the Production Examples and the acrylic resin compositions obtained in the Examples and Comparative Examples were injection molded under the conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain rectangular test pieces having a thickness of 4 mm, a long side of 80 mm, and a short side of 10 mm. The flexural modulus of each test piece was measured using a precision universal testing machine Autograph AG-IS5kN, manufactured by Shimadzu Corporation, in accordance with the method described in JIS K7171.
[0154] (saturated water absorption rate) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the acrylic copolymer obtained in the manufacturing example and the acrylic resin composition obtained in the examples and comparative examples were injection molded under the conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec to obtain a square test piece having a thickness of 3 mm and a side length of 50 mm. The test piece was vacuum dried for 24 hours under conditions of a temperature of 80°C and 5 mmHg. The test piece was then allowed to cool in a desiccator. The test piece was taken out of the desiccator and the mass (initial mass) was measured immediately. The test piece was then immersed in distilled water at 23°C. The test piece was taken out of the water, the water adhering to the surface was wiped off, and the mass was measured. Immersion in distilled water and mass measurement were repeated until there was no change in mass. The saturated water absorption rate was calculated from the mass (absorbed mass) when there was no change in mass and the initial mass by the following formula. Saturated water absorption rate (%) = [(absorbed mass - initial mass) / initial mass] × 100
[0155] (Moldability) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the acrylic resin compositions obtained in the examples and comparative examples were injection molded under conditions of a cylinder temperature of 280°C, a mold temperature of 75°C, and a molding cycle of 1 minute to produce flat plates with a length of 205 mm, a width of 160 mm, and a thickness of 0.5 mm. The ratio of the resin flow length (190 mm) to the thickness was 380. In addition, the acrylic resin compositions obtained in the Examples and Comparative Examples were extruded from a 150 mm wide T-die at a resin temperature of 260°C using a single screw extruder with a shaft diameter of 20 m to obtain a single layer film with a width of 100 mm and a thickness of 80 μm. The appearance of the plate was visually observed. The moldability was judged based on the presence or absence of molding defects such as sink marks and silver spots. The appearance of the film was also visually observed. The moldability was judged based on the presence or absence of bubbles and gel particles. ○: No sink marks on the molded product, no silver spots, no foaming in the film, and no gel particles. ×: Sink marks or silver spots were observed on the molded product, or bubbles or gel particles were observed on the film.
[0156] (Dimensional stability) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the acrylic resin compositions obtained in the examples and comparative examples were injection molded under conditions of a cylinder temperature of 280°C, a mold temperature of 75°C, and a molding cycle of 1 minute to produce flat plates with a length of 205 mm, a width of 160 mm, and a thickness of 0.5 mm. The ratio of the resin flow length (190 mm) to the thickness was 380. The flat plates were placed in either (1) an incubator with a temperature of 60°C and a relative humidity of 90%, or (2) a thermostat with a temperature of 90°C and a relative humidity of 60%, and left in the air for 500 hours. The flat plates were then removed from the incubators and their lengthwise dimensions were measured. The dimensional change rate from the lengthwise dimensions before placing them in the incubators was calculated. Under both conditions (1) and (2), the dimensional change rate is 0.3% or less, and The dimensional change rate under either condition (1) or (2) is 0.3% or less. In both conditions (1) and (2), the dimensional change rate was determined to be greater than 0.3%.
[0157] (Pencil hardness) Using an injection molding machine (M-100C, manufactured by Meiki Seisakusho Co., Ltd.), the acrylic resin compositions obtained in the Examples and Comparative Examples were injection molded under conditions of a cylinder temperature of 260°C, a mold temperature of 50°C, and an injection speed of 50 mm / sec, to obtain square test pieces with a thickness of 3 mm and a side length of 50 mm. In addition, the acrylic resin compositions obtained in the Examples and Comparative Examples were extruded from a 150 mm wide T-die at a resin temperature of 260°C using a single screw extruder with a shaft diameter of 20 m to obtain a single layer film with a width of 100 mm and a thickness of 80 μm. The pencil hardness of each test piece and single layer film was measured under a load of 0.75 kg in accordance with JIS K5600-5-4. ○: Pencil hardness of test specimen and single layer film is H or higher ×: Pencil hardness of test piece or single layer film is F or less
[0158] (Precursor polymer) The precursor polymers Aa to Af and Ah used in this production example were produced by the following method. Precursor polymers Aa-Af and Ah In an autoclave equipped with a stirrer, purified methyl methacrylate (MMA), α-methylstyrene (αMSt), styrene (St), 2,2'-azobis(2-methylpropionitrile) (AIBN) and n-octyl mercaptan (n-OM) were charged in the ratios shown in Table 1, and uniformly dissolved to obtain polymerization raw materials. Nitrogen gas was blown into the reaction raw materials to remove dissolved oxygen to 3 ppm. Then, the atmosphere in a continuous flow tank reactor equipped with a brine cooling condenser was replaced with nitrogen gas. The polymerization raw materials were continuously supplied to the tank reactor at a constant flow rate so as to obtain the average residence time shown in Table 1, and bulk polymerization was performed at the polymerization temperature shown in Table 1, and a liquid containing a precursor polymer was continuously discharged from the tank reactor. The pressure in the tank reactor was adjusted by a pressure regulating valve connected to the brine cooling condenser. The polymerization conversion rate became the value shown in Table 1. The liquid discharged from the reactor was then heated to 230°C and fed to a twin-screw extruder controlled at 240°C. In the twin-screw extruder, volatile components mainly composed of unreacted monomers were separated and removed, and the precursor polymer was extruded as strands. The strands were cut with a pelletizer to obtain a precursor polymer. The weight average molecular weight Mw, the proportion of each monomer unit, and the glass transition temperature of the obtained precursor polymer were measured. The results are shown in Table 1.
[0159] Precursor polymer Ag An MS resin (a copolymer of methyl methacrylate (MMA) and styrene (St)) was produced according to the method for producing copolymer (A) described in the section [Examples] of JP 2003-231785 A. By changing the mass ratio of MMA, St, and t-dodecyl mercaptan (t-DM) charged in an autoclave, a precursor polymer Ag; Mw = 95,000, Tg = 116°C, and a styrene monomer unit content of 10 mass% was obtained.
[0160] (Acrylic copolymer (A)) Manufacturing Example 1 The acrylic copolymer [Aa] was fed at 10 kg / hr to the conveying section of a twin-screw extruder (manufactured by Nippon Steel Corporation; product name TEX30α-77AW-3V) which was composed of a conveying section, a melt-kneading section, a devolatilizing section, and a discharge section, and was set at a screw speed of 100 rpm and a temperature of 230°C. In the melt-kneading section in which a kneading block was installed, the amount of monomethylamine added was adjusted so that the content of the structural unit derived from glutarimide in Table 1 was obtained, and the monomethylamine was injected from the additive supply port of the twin-screw extruder, and the acrylic copolymer [Aa] was reacted with the monomethylamine. The melt-kneading section was mostly composed of kneading disks, and sealing elements were attached to both ends of the kneading disks. In the devolatilizing section, by-products and excess monomethylamine were volatilized from the molten resin which had passed through the melt-kneading section, and discharged through multiple vents. The molten resin extruded as a strand from the die at the end of the discharge section of the twin-screw extruder was cooled in a water tank and then cut with a pelletizer to obtain pelletized imidized resin [A-1]. The content of structural units derived from glutarimide in imidized resin [A-1] was 9 wt%. The composition and physical properties of imidized resin [A-1] are shown in Table 1.
[0161] Manufacturing Example 2 Except for using the acrylic copolymer [Ab] instead of the acrylic copolymer [Aa] and changing the amount of monomethylamine added so that the content of structural units derived from glutarimide was 7 wt%, an imidized resin [A-2] was obtained in the same manner as in Example 1. The composition and physical properties of the imidized resin [A-2] are shown in Table 1.
[0162] Production Example 3 Except for using the acrylic copolymer [Ab] instead of the acrylic copolymer [Aa] and changing the amount of monomethylamine added so that the content of structural units derived from glutarimide was 15 wt%, an imidized resin [A-3] was obtained in the same manner as in Example 1. The composition and physical properties of the imidized resin [A-3] are shown in Table 1.
[0163] Production Example 4 An imidized resin [A-4] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ac] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 8 wt%. The composition and physical properties of the imidized resin [A-4] are shown in Table 1.
[0164] Production Example 5 An imidized resin [A-5] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ad] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 9 wt%. The composition and physical properties of the imidized resin [A-5] are shown in Table 1.
[0165] Production Example 6 An imidized resin [A-6] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ad] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 23 wt%. The composition and physical properties of the imidized resin [A-6] are shown in Table 1.
[0166] Production Example 7 An imidized resin [A-7] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ad] was used instead of the acrylic copolymer [Aa], and the amount of ammonia added instead of monomethylamine was changed so that the content of structural units derived from glutarimide was 15 wt%. The composition and physical properties of the imidized resin [A-7] are shown in Table 1.
[0167] Production Example 8 An imidized resin [A-8] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ae] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 19 wt%. The composition and physical properties of the imidized resin [A-8] are shown in Table 1.
[0168] Production Example 9 An imidized resin [A-9] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Af] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 12 wt%. The composition and physical properties of the imidized resin [A-9] are shown in Table 1.
[0169] Manufacturing Example 10 An imidized resin [A-10] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ab] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 45 wt%. The composition and physical properties of the imidized resin [A-10] are shown in Table 1.
[0170] Manufacturing Example 11 An imidized resin [A-11] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ag] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 10 wt%. The composition and physical properties of the imidized resin [A-11] are shown in Table 1.
[0171] Manufacturing Example 12 An imidized resin [A-12] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ag] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 44 wt%. The composition and physical properties of the imidized resin [A-12] are shown in Table 1.
[0172] Manufacturing Example 13 An imidized resin [A-13] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ah] was used instead of the acrylic copolymer [Aa] and the amount of monomethylamine added was changed so that the content of structural units derived from glutarimide was 24 wt%. The composition and physical properties of the imidized resin [A-13] are shown in Table 1.
[0173] Manufacturing Example 14 An imidized resin [A-14] was obtained in the same manner as in Example 1, except that the acrylic copolymer [Ab] was used instead of the acrylic copolymer [Aa] and the copolymer was passed through the extruder without adding an imidizing agent. The composition and physical properties of the imidized resin [A-14] are shown in Table 1.
[0174] [Table 1]
[0175] (Elastomer) Manufacturing Example 15 In a reactor equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a monomer inlet tube and a reflux condenser, 1050 parts by mass of ion-exchanged water, 0.44 parts by mass of sodium polyoxyethylene tridecyl ether acetate and 0.7 parts by mass of sodium carbonate were charged, and the inside of the reactor was fully replaced with nitrogen gas. The inside temperature was then set to 80°C. 0.25 parts by mass of potassium persulfate was added thereto and stirred for 5 minutes. 245 parts by mass of a monomer mixture consisting of 95.4% by mass of methyl methacrylate, 4.4% by mass of methyl acrylate and 0.2% by mass of allyl methacrylate was continuously dropped into the mixture over a period of 60 minutes. After the dropwise addition, the polymerization reaction was continued for another 30 minutes so that the polymerization conversion rate was 98% or more. Next, 0.32 parts by mass of potassium persulfate was added to the reactor and stirred for 5 minutes. After that, 315 parts by mass of a monomer mixture consisting of 80.5% by mass of butyl acrylate, 17.5% by mass of styrene, and 2% by mass of allyl methacrylate was continuously added dropwise over 60 minutes. After the dropwise addition was completed, the polymerization reaction was continued for another 30 minutes so that the polymerization conversion rate was 98% or more. Next, 0.14 parts by mass of potassium persulfate was added to the reactor and stirred for 5 minutes. Then, 140 parts by mass of a monomer mixture consisting of 95.2% by mass of methyl methacrylate, 4.4% by mass of methyl acrylate, and 0.4% by mass of n-octyl mercaptan was continuously dropped over 30 minutes. After the dropwise addition was completed, the polymerization reaction was continued for another 60 minutes so that the polymerization conversion rate was 98% or more. By the above operations, a latex containing a multilayer copolymer elastomer was obtained. The latex was frozen and coagulated. It was then washed with water and dried to obtain a multilayer copolymer elastomer (B-1). The average particle size of the multilayer copolymer elastomer (B-1) was 0.2 μm.
[0176] Manufacturing Example 16 In a pressure autoclave, 150 parts by mass of ion-exchanged water, 85 parts by mass of 1,3-butadiene, 15 parts by mass of styrene, 0.5 parts by mass of t-dodecyl mercaptan, 0.4 parts by mass of diisopropylbenzene hydroperoxide, 1.5 parts by mass of sodium pyrophosphate, 0.02 parts by mass of ferrous sulfate, 1.0 part by mass of dextrose, and 1.0 part by mass of potassium oleate were charged and reacted with stirring at 50°C for 15 hours to produce a butadiene-based rubber polymerization latex.
[0177] 65 parts of the butadiene rubber polymerized latex (as solids) was charged into a flask, and after replacing with nitrogen, 1.2 parts by mass of NaHCO3 was added as a 10% aqueous solution, and the mixture was stirred for 30 minutes. 1 part of potassium oleate was added as a 7% aqueous solution to this liquid for stabilization. Then, 0.6 parts by mass of Rongalit was added, and the liquid temperature was kept at 70°C, and 35 parts by mass of a monomer mixture having the following composition was graft-polymerized to the butadiene rubber polymerized latex.
[0178] Per 100 parts by mass of the total graft monomer mixture, a mixture of 40 parts by mass of methyl methacrylate, 5 parts by mass of ethyl acrylate, and 0.1 parts by mass of t-butyl hydroperoxide (t-BH) was added dropwise over 1 hour as a monomer mixture for the first graft stage, and the mixture was polymerized by continuing stirring for 2 hours. Thereafter, a mixture of 40 parts by mass of styrene and 0.1 parts by mass of t-BH was added dropwise over 1 hour as a monomer mixture for the second graft stage, and the mixture was polymerized by continuing stirring for 2 hours. Finally, a mixture of 15 parts by mass of methyl methacrylate and 0.05 parts by mass of t-BH was added dropwise over 1 hour as a monomer mixture for the third graft stage, and the mixture was polymerized by continuing stirring for 2 hours to obtain a latex of multilayer copolymer elastomer (B-2).
[0179] 0.5 parts by mass of BHT was added to the obtained multi-layer copolymer elastomer (B-2) latex, and then 0.2% sulfuric acid aqueous solution was added to coagulate the multi-layer copolymer elastomer (B-2), which was then heat-treated and solidified at 90°C. The coagulated product was then washed with warm water and further dried to obtain a multi-layer copolymer elastomer (B-2) powder. The average particle size of the multi-layer copolymer elastomer (B-2) was 0.2 μm.
[0180] Manufacturing Example 17 A 3m glass-lined tank with a jacket and stirrer that can be cooled with brine and whose interior has been degassed and replaced with nitrogen. 3 A reaction vessel was charged with 735 kg of dry toluene, 0.4 kg of hexamethyltriethylenetetramine, and 39.4 kg of a toluene solution containing 20 mol of isobutylbis(2,6-di-t-butyl-4-methylphenoxy)aluminum at room temperature, and further charged with 1.17 mol of sec-butyllithium. 35.0 kg of methyl methacrylate was added thereto, and the mixture was reacted at room temperature for 1 hour to obtain a methyl methacrylate polymer (polymer block (b1-1)) having a weight average molecular weight (hereinafter referred to as Mw(b1-1)) of 40,000.
[0181] Next, while keeping the reaction vessel at -25°C, a mixture of 24.5 kg of n-butyl acrylate and 10.5 kg of benzyl acrylate was added dropwise over 0.5 hours to grow a polymer block (b2) consisting of a copolymer of n-butyl acrylate and benzyl acrylate from one end of the polymer block (b1-1), thereby obtaining a diblock copolymer elastomer (B-3) having a weight average molecular weight of 80,000. Since the weight average molecular weight of the polymer block (b1-1) was 40,000, the weight average molecular weight (Mw(b2)) of the polymer block (b2) was determined to be 40,000. The diblock copolymer elastomer (B-3) has an acrylic acid ester content of 50% by mass.
[0182] Example 1 80 parts by mass of the acrylic copolymer (A-1) and 20 parts by mass of the multilayer copolymer elastomer (B-1) were mixed together, melt-kneaded at 250° C. in a twin-screw extruder having a shaft diameter of 20 mm, and extruded to obtain a pellet-shaped acrylic resin composition (C-1) having a glass transition temperature of 120° C. The evaluation results are shown in Table 2.
[0183] Examples 2 to 12 An acrylic resin composition was obtained in the same manner as in Example 1, except for the formulation shown in Table 2. The evaluation results are shown in Table 2.
[0184] [Table 2]
[0185] Comparative Examples 1 to 7 An acrylic resin composition was obtained in the same manner as in Example 1, except for the formulation shown in Table 2. The evaluation results are shown in Table 3.
[0186] [Table 3]
[0187] As shown in Tables 1 to 3, the acrylic resin composition of the present invention contains an acrylic copolymer that has an excellent balance of heat resistance, low water absorption, and thermal decomposition resistance, and therefore maintains high heat resistance, low water absorption, and high rigidity even when an elastomer is added, and has good thermal stability. The acrylic resin composition of the present invention can provide molded articles and films that are excellent in dimensional stability, moldability, and surface hardness.
Claims
1. An acrylic resin composition comprising 51 to 99 mass% of an acrylic copolymer (A) comprising 30 to 87 mass% of methyl methacrylate units, 6 to 40 mass% of structural units (R) having at least one ring structure in the main chain selected from the group consisting of glutaric anhydride units and N-substituted or unsubstituted glutarimide units, 7 to 30 mass% of α-methylstyrene units, and 0 to 20 mass% of other vinyl monomer units (C) copolymerizable with methyl methacrylate, and 1 to 49 mass% of an elastomer (B), An acrylic resin composition having a molded product with a softening temperature of 110°C or higher, as measured according to the method specified in JIS K7206 B50.
2. The acrylic resin composition according to claim 1, wherein the structural unit (R) is an N-substituted glutarimide unit represented by formula (I). 【Chemistry 1】 (In formula (I), R 1 are each independently a hydrogen atom or a methyl group; R 2 is an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an organic group having 6 to 15 carbon atoms and containing an aromatic ring.
3. The acrylic resin composition according to claim 1 or 2, wherein the other vinyl monomer unit (C) copolymerizable with the methyl methacrylate unit is formed of at least one monomer selected from the group consisting of an acrylic acid ester monomer, an aromatic vinyl monomer, and a vinyl cyanide monomer.
4. The acrylic resin composition according to any one of claims 1 to 3, wherein the other vinyl monomer unit (C) copolymerizable with the methyl methacrylate unit is formed of at least one selected from the group consisting of methyl acrylate, ethyl acrylate, styrene, and acrylonitrile.
5. The acrylic resin composition according to any one of claims 1 to 3, wherein the other vinyl monomer unit (C) copolymerizable with the methyl methacrylate unit is formed by styrene.
6. The acrylic resin composition according to any one of claims 1 to 5, wherein the elastomer (B) contains a multilayer copolymer elastomer having a methacrylic acid ester unit and an acrylic acid ester unit.
7. The acrylic resin composition according to any one of claims 1 to 6, wherein the elastomer (B) contains a block copolymer elastomer composed of a polymer block (b1) having a methacrylic acid ester unit and a polymer block (b2) having an acrylic acid ester unit.
8. The acrylic resin composition according to any one of claims 1 to 7, which has a saturated water absorption rate of 2.5% or less.
9. A molded article comprising the acrylic resin composition according to any one of claims 1 to 8.
10. A film comprising the acrylic resin composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Imide polymer
JP1987089705A
Optical disk substrate
JP1988163301A
Glass fiber-reinforced thermoplastic resin
JP1989261445A
Resin composition
JP1989315461A
Film for protecting polarizing film
JP1993119217A